Movement Instruction to Facilitate Beat Competency in Instrumental Music. (March 2014) - Conway, Colleen; Marshall, Herbert; Hartz, Barry
This article offers instrumental directors at all levels some suggestions for the use of movement to facilitate beat competency. We use the term beat competency to refer to a musician's ability to play with a consistent sense of pulse and balanced subdivision, as well as the eventual ability to bring that sense of pulse to reading rhythmic notation. We discuss movement instruction with a focus on the ideas of Rudolf Laban. We present instructional strategies for movement through Laban's concepts of flow, weight, space, and time. The final section of the article addresses the challenges in using movement in instrumental music and provides suggestions for working with large ensembles as well as focusing on performance.